Changes in membrane glycoproteins of circulating platelets after coronary stent implantation. Issue 2 (August 1996) - Gawaz, M.; Neumann, F. J.; Ott, I.; May, A.; Rüdiger, S.; Schömig, A.
Abstract : OBJECTIVES: To evaluate platelet function in patients with coronary stents. DESIGN: A non-randomised control trial in 30 patients who had immediate implantation of Palmaz-Schatz coronary stents because of a suboptimal angioplasty result. All patients received a standardised anticoagulation regimen including intravenous heparin (activated partial thromboplastin time (APTT) 80 to 120 s), oral vitamin K antagonist (target international normalised ratio (INR) of 3.5), and 100 mg aspirin twice daily. Platelet surface expression of glycoprotein IIb-IIIa, activated fibrinogen receptor, and P-selectin as well as binding of von Willebrand factor and fibrinogen were determined by flow cytometry in peripheral venous blood samples collected before the intervention and then daily for 4 days after it. The results were compared with those in 30 patients undergoing elective coronary balloon angioplasty. SETTING: University hospital. RESULTS: After coronary stenting surface expression of the activated fibrinogen receptor significantly increased, peaking at day 2 (P < 0.001). Similar results were found for von Willebrand factor binding and P-selectin surface expression, with a maximum at day 2 to 4 after stenting (von Willebrand factor, P < 0.001; P-selectin, P < 0.001). The changes in platelet membrane glycoproteins coincided with a significant drop in peripheral platelet count after stent placement (P < 0.01). No significant change in fibrinogen receptor activity, von Willebrand factor binding, P-selectin surface expression, or platelet count was seen in the control group. CONCLUSIONS: The present study shows that current anticoagulation treatment is inefficient in suppressing platelet activation in patients with coronary stents and, therefore, might not be the best treatment for reducing the incidence of subacute stent thrombosis.